Perceiving Emotion: Scripts Versus Emotion Concepts. - Eickers, Gen (Erkenntnis, 2026)
This paper proposes that the role of emotion scripts, and their entanglement with emotion concepts, has not been adequately treated in recent concept-focused and situated approaches to emotion perception. These approaches aim to emphasize the context-sensitive and interactive nature of emotion perception, and I argue that scripts have distinctive explanatory power when it comes to both of these features of emotion perception, and accordingly deserve to be taken more seriously by concept-focused and situated approaches. Situated perspectives on emotion perception have long pointed out that, while the move toward understanding emotion perception as context-sensitive is needed, an individualistic and overly cognitive focus remains in context-sensitive accounts to emotion perception, particularly in accounts that emphasize emotion concepts (See Glazer 2022, Krueger 2014a, Krueger 2014b). And while recent and influential context-sensitive approaches to emotion perception have emphasized emotion concepts (see Gendron & Barrett, 2018), earlier work on emotion concepts that ties them to emotion scripts has been ignored in these recent views (e.g., Russell 1991, Russell, 2003; Wierzbicka, 1999; Fehr & Russell, 1984). Situated approaches that criticize recent context-sensitive views for their individualistic focus have also overlooked scripts, despite their potential to contribute to situated views. Overlooking scripts is a problem when arguing for a context-sensitive and situated understanding of emotion perception. Scripts describe contextually variable, normatively constrained moves between social agents; that is, they account for how social norms influence social interaction (including emotion perception) in context-sensitive ways. Thus, scripts are exceptionally well positioned to account for context-sensitive, interactive emotion perception. This paper aims to (1) explain what it means to understand emotion perception as both interactive and context-sensitive, making reference to situated approaches to emotion perception, and (2) bring scripts back into the debate on emotion perception.